METODE “CANVAS BUSINESS MODEL” MENINGKATKAN PRODUKTIVITAS BUMDES - Wahyudi, Heru; Ciptawaty, Ukhti; Marselina, Marselina; Ambya, Ambya; Suparta, I Wayan (Faculty of Economics and Business Lampung University, 2024)
There is a reality that the BUM Desa village development goals plan is not implemented in accordance with the development master. Regarding the administration and structure of BUM Desa and the utilization of BUM Village funds, many violations and irregularities have been discovered. Purworejo Village, Pesawaran Regency, also revealed shortcomings in the management of Village BUM. The management of BUM DES in Purworejo Village is hit by three main issues: those related to the organization's potential as an economic, social and human resource. Academic support can help BUM DESA Purworejo, Pesawaran Regency overcome three challenges. As a result, the assistance that can be provided to Purworejo Village must focus on general business management, business administration, and business feasibility science. Development economics academics can offer hands-on instruction and experience with corporate feasibility studies and feasibility studies. In addition, from a scientific point of view, business administration can help strengthen the management and administration of the BUM DES business unit, which has not yet produced at its peak level and has even been suspended. Here, BUM DES constantly faces losses and failures. Apart from that, this support will also be combined with training on work motivation for Purworejo Village residents.